Grandparents to Grandchildren Transfers: The Potential Importance to Younger Families’ Economic Stability - Fontes, Angela; Holden, Karen (My University, 2008)
Grandparents are more likely to give time and money to their grandchildren's families when grandparents are young, married and financially secure. They are more likely to assist grandchildren if they themselves were assisted or assisted their own children. Grandparents who continue to work are more likely to provide time and money assistance than nonworking grandparents, even controlling for age and income of grandparents. The authors conclude that grandparents may adjust their retirement plans to enable their adult children to fulfill child-rearing needs.